Complexity of Host Micro‐RNA Response to Cytomegalovirus Reactivation After Organ Transplantation. Issue 2 (13th October 2015) - Egli, A.; Lisboa, L. F.; O'Shea, D.; Asberg, A.; Mueller, T.; Emery, V.; Kumar, D.; Humar, A.
Abstract : Human ( Homo sapiens ) micro‐RNAs (hsa‐miRNAs) regulate virus and host‐gene translation, but the biological impact in patients with human cytomegalovirus (hCMV) infection is not well defined in a clinically relevant model. First, we compared hsa‐miRNA expression profiles in peripheral blood mononuclear cells from 35 transplant recipients with and without CMV viremia by using a microarray chip covering 847 hsa‐miRNAs. This approach demonstrated a set of 142 differentially expressed hsa‐miRNAs. Next, we examined the effect of each of these miRNAs on viral growth by using human fibroblasts (human foreskin fibroblast‐1) infected with the hCMV Towne strain, identifying a subset of proviral and antiviral hsa‐miRNAs. miRNA‐target prediction software indicated potential binding sites within the hCMV genome (e.g., hCMV‐UL52 and ‐UL100 [UL = unique long]) and host‐genes (e.g., interleukin‐1 receptor, IRF1 ). Luciferase‐expressing plasmid constructs and immunoblotting confirmed several predicted miRNA targets. Finally, we determined the expression of selected proviral and antiviral hsa‐miRNAs in 242 transplant recipients with hCMV‐viremia. We measured hsa‐miRNAs before and after antiviral therapy and correlated hsa‐miRNA expression levels to hCMV‐replication dynamics. One of six antiviral hsa‐miRNAs showed a significant increase during treatment, concurrent with viral decline. In contrast, six of eight proviral hsa‐miRNAs showed a decrease during viral decline. Our results indicate that a complex and multitargeted hsa‐miRNA response occurs during CMV replication in immunosuppressed patients. This study provides mechanistic insight and potential novel biomarkers for CMV replication.